PenambahanTepung Bonggol Pisang sebagai Substitusi Tapioka terhadap Kualitas Kimia dan Organoleptik Bakso: Burning Quality of Biocharcoal Briquettes Mixed of Goat Dung and Lontar Shell (Saboak) with Different Levels of Adhesive - Natalia Kolo; Agustinus R. Riwu; Heri Armadianto, (Universitas Nusa Cendana, 2023)
Banana weevil flour is widely used as a food additive, so it is expected to be an alternative as asubstitute for tapioca which diffuses as a filler and binder. Experiments were conducted with the aimof substituting tapioca with coco banana weevil flour against the chemical and organoleptic qualities ofbeef meatballs. Research materials include beef, banana pupae weevil flour, tapioca flour, as well asother additives such as spices. The Complete Randomized Design (RAL) was used in this study whichconsisted of 5 treatments, namely the substitution of banana weevil flour: 0%, 5%, 10%, 15% and 20%and 3 repeats. The parameters studied are chemical quality tests which include (fat, protein, andcarbohydrate content) and organoleptic tests which include (taste, aroma, and color). The results of theanalysis showed that the substitution of banana weevil flour had a noticeable influence (P<.0.05) onchemical and organoleptic quality. It is concluded that banana weevil flour can replace tapioca inmeatball processing and substitution at the level of 5% can produce low fat, relatively good taste andaroma. The substitution of 10% banana puck boggol flour can produce high protein and to producehigh carbohydrates and the best color can be used banana weevil flour as much as 15%. Penelitian bertujuan mengetahui kualitas bakar briket bioarang campuran arang kotoran kambing dan tempurung saboak dengan level perekat berbeda. Materi yang digunakan adalah kotoran kambing 8 kg, tempurung saboak 8 kg, tapioka 1,5 kg dan air. Metode yang digunakan yaitu Rancangan Acak Lengkap (RAL) dengan 4 perlakuan dan 4 ulangan. Perlakuan level perekat dari bahan bioarang yaitu P1: 6%, P2: 8%, P3: 10%, dan P4: 12%; proporsi kotoran kambing dan tempurung saboak masing-masing 500 gram. Variabel yang diteliti: temperatur bakar, laju pembakaran, ketahanan bakar, warna dan asap serta kemampuan mendidihkan air. Data dianalisis dengan analisis keragaman (ANOVA). Hasil analisis menunjukkan perlakuan berpengaruh nyata (P<0,05) terhadap temperatur bakar, berpengaruh tidak nyata (P>0,05) terhadap laju pembakaran, ketahanan bakar, warna dan asap serta kemampuan mendidihkan air. Temperatur bakar briket bioarang yang didapatkan berkisar 154,17-214,09oC; laju pembakaran 2,14-2,44g/menit; ketahanan bakar 164-188 menit; skor warna pembakaran 2,8-4 (cenderung merah - merah kebiruan) dan skor asap 3,85-4 (cenderung tidak ada asap - tidak ada asap) dan kemampuan mendidihkan air 19,5-27,75 menit. Disimpulkan bahwa naiknya level perekat menurunkan temperatur bakar tapi tidak menyebabkan perubahan laju pembakaran, ketahanan bakar, warna dan asap pembakaran serta kemampuan mendidihkan air. Kualitas bakar terbaik didapatkan pada P1 yaitu penggunaan level perekat 6%.